PENGARUH FUNGI Mikoriza arbuskula DAN PUPUK FOSFAT TERHADAP PERTUMBUHAN SERTA HASIL TANAMAN JAGUNG PULUT (Zea mays ceritina kulesh) PADA TANAH PODSOLIK MERAH KUNING - Budi Fitriani; Iwan Sasli; Fadjar Rianto (Partner, 2021)
The study aims to determine the effect of the application arbuscular mycorrhizal fungi, phosphate fertilizers on the growth and yield of white corn on ultisol soil. The research method used a factorial randomized block design. The first factor was the use of mycorrhizal fungi (without mycorrhizae, and given mycorrhizae) and the second factor was the dose of phosphate per plant (5 g/plant, 4 g/plant, 2 g/plant, 1 g/plant, and 0 g/plant). There is an interaction effect of inoculation dose of AMF and P on cob and cob weight variables. The AMF treatment significantly affected the weight of the cobs with the cobs, the weight of the cobs without the cobs, the number of seeds per ear and the number of mycorrhizal spores. The dose of P fertilizer affected the variable weight of cobs with cobs, weight of cobs without cobs, length of ears and number of seeds per ear. Key words: AMF, cobs, corn husks, marginal land, phosphate fertilizer